Minimum Wage Policy with Optimal Taxes and Unemployment - Lavecchia, Adam M. (Université d'Ottawa | University of Ottawa, 2018)
This paper sheds new light on the desirability of the minimum wage in the presence of an optimal non-linear income tax. Using a search-and-matching framework, I derive a novel condition that links the desirability of the minimum wage to three sufficient statistics: (1) the macro or general equilibrium labor force participation response to the minimum wage by low-skilled individuals; (2) the macro employment response to the minimum wage for low-skilled individuals; and (3) the welfare weight on low-skilled workers. This condition shows that the minimum wage is welfare improving if it pushes the labor market tightness – the ratio of the aggregate number of vacancies to low-skilled job seekers – closer to its efficient level. Guided by the theory, I estimate the first two sufficient statistics using an event study design, as well as state and federal minimum wage variation between 1979-2014. I estimate a macro participation elasticity of -0.24 and a macro employment elasticity of -0.32. The former represents new evidence on a previously overlooked margin of the minimum wage. With these estimates in hand, I simulate the total welfare gains from introducing a minimum wage beginning from the optimal income tax allocation. The simulations show that the minimum wage is welfare improving only if the government has very strong redistributive tastes.
Keywords: minimum wage; sufficient statistics; optimal policy; labor force participation